Introgression of the Triticum timopheevii Genome Into Wheat Detected by Chromosome-Specific Kompetitive Allele Specific PCR Markers - King, Julie; Grewal, Surbhi; Othmeni, Manel; Coombes, Benedict; Yang, Cai-yun; Walter, Nicola; Ashling, Stephen; Scholefield, Duncan; Walker, Jack; Hubbart-Edwards, Stella; Hall, Anthony; King, Ian Phillip (Frontiers in Plant Science, 2022)
Triticum timopheevii (2n=28, AtAtGG) is a tetraploid wild relative species with great potential to increase the genetic diversity of hexaploid wheat Triticum aestivum (2n=42, AABBDD) for various important agronomic traits. A breeding scheme that propagated advanced backcrossed populations of wheat-T. timopheevii introgression lines through further backcrossing and self-fertilisation resulted in the generation of 99 introgression lines (ILs) that carried 309 homozygous segments from the At and G subgenomes of T. timopheevii. These introgressions contained 89 and 74 unique segments from the At and G subgenomes, respectively. These overlapping segments covered 98.9% of the T. timopheevii genome that has now been introgressed into bread wheat cv. Paragon including the entirety of all T. timopheevii chromosomes via varying sized segments except for chromosomes 3At, 4G and 6G. Homozygous ILs contained between one and eight of these introgressions with an average of three per introgression line. These homozygous introgressions were detected through the development of a set of 480 chromosome-specific Kompetitive allele specific PCR (KASP) markers that are well-distributed across the wheat genome. Of these, 149 were developed in this study based on single nucleotide polymorphisms (SNPs) discovered through whole genome sequencing of T. timopheevii. A majority of these KASP markers were also found to be T. timopheevii subgenome specific with 182 detecting At subgenome and 275 detecting G subgenome segments. These markers showed that 98% of the At segments had recombined with the A genome of wheat and 74% of the G genome segments had recombined with the B genome of wheat with the rest recombining with the D genome of wheat. These results were validated through multi-colour in situ hybridisation analysis. Together these homozygous wheat-T. timopheevii ILs and chromosome-specific KASP markers provide an invaluable resource to wheat breeders for trait discovery to combat biotic and abiotic stress factors affecting wheat production due to climate change.